TARI KREASI SAGUNG WAH - I Gusti Ayu Agung Adi Sartika Dewi; Ni Made Arshiniwati; Gusti Ayu Ketut Suandewi (UPT Pusat Penerbitan LP2MPP Institut Seni Indonesia Denpasar, 2021)
Sagung Wah's dance was inspired by the heroic story of Sagung Ayu Wah as a young woman who fought against the invading forces who wanted to rule her kingdom, the Kingdom of Tabanan. The story of Sagung Wah's struggle is also written in the Chronicle of Arya Tabanan and Queen of Tabanan. The heroic story of Sagung Ayu Wah was then poured into the form of dance creations. Kreasi baru dance is a type of dance that has been given a directed pattern that has been developed and refined so that it can create a new movement pattern. The creator chooses dance movements that are created but still based on traditional motion patterns in order to gain freedom in moving and imagination.The method that the creator used in working on this dance work is alma M. Hawkins creation method consisting of exploration, improvisation, and forming stage. The three methods were successfully applied in working on this work with dance supporters. The purpose of the creation of this dance creation is to commemorate the story and services of a Sagung Wah in defending the tabanan kingdom as well as a form of appreciation as a woman of Tabanan region.Sagung Wah dance created by eight dancers consists of five female dancers and three male dancers. Makeup on this film uses soft makeup but still sharpens the eyes to fit the concept of clothing used. The dress of this work combines the colors between white which has a sacred meaning and the colors gold and black will look magnificent and authoritative. The dance creations of Sagung Wah are packaged in five structures, namely, flashback, papeson, pangawak, pangecet, pasiat, and panyuwud. The 12-minute directed is accompanied by Semara Pegulingan gamelan.Keywords: Sagung Wah, Tabanan Kingdom, Dance Creations, Creatio.